COMMON ALLERGIC ATTENDANT’S SITUATIONS TO SPECIALIZED ALLERGY CENTER / KIRKUK (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Rising participation rates in epidemiologic studies using postal questionnaires pose a threat to the validity of these research's basic data collection efforts. This study surveyed 1021 patients who visited the Allergy Center in Kirkuke between September 2017 and March 2018 as part of a larger cross. Sectional evaluation of respiratory health in order to determine whether there was an association between disease and either sex or age. Patients with pharyngitis, acute tonsillitis, throat pain, influenza, pneumonia, sinusitis, tonsillar abscess, respiratory diseases, bronchitis, pulmonary emphysema, asthma, bronchitis, and other acute infections were found to have significantly different odds of contracting these diseases based on their gender (P 0.05). The statistical analysis revealed that there were significant variations in the likelihood of infection between the sexes, with a p.value of less than 0.05, indicating that females were more likely to experience allergies. Additionally, when looking at the correlation between illness and age across all age groups, statistical analysis revealed that the 45–64 year old bracket had the greatest impact, followed by the 1–14 age bracket.Out of all the,disorders examined, sinusitis and asthma were the most common across all five age groups.